1997
DOI: 10.1007/s11626-997-0156-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of embryonic chick insulin cells in culture: Beneficial effects of serum-free medium, raised nutrients, and biomatrix

Abstract: A previous finding that insulin cells do not survive or differentiate in explants of embryonic avian pancreas cultured in collagen gel with a serum-containing medium has provided a model system for identification of conditions favorable for development of these cells. To this end, we here modify the substrate and the medium. The epithelial component of dorsal pancreatic buds of 5-d chick embryos was cultured for 7 d on Matrigel in serum-containing and in serum-free medium, the latter incorporating insulin, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…Replacement of collagen gel with Matrigel, culture conditions otherwise remaining identical, also resulted in a significant increase in the proportion of insulin cells (from 0.2 to 3.1%). This indicates that for survival and development of insulin cells, Matrigel is superior to collagen gel (Rawdon and Andrew, 1997). This finding is in line with results of studies on mammalian islet cells that have shown extracellular matrix produced by cultured bovine corneal endothelial cells (Beattie et al, 1991;Hayek et al, 1989) or by a basement membrane-secreting tumour line (Muschel et al, 1986) to improve islet cell function.…”
Section: Effect Of Substrate and Mediumsupporting
confidence: 85%
See 1 more Smart Citation
“…Replacement of collagen gel with Matrigel, culture conditions otherwise remaining identical, also resulted in a significant increase in the proportion of insulin cells (from 0.2 to 3.1%). This indicates that for survival and development of insulin cells, Matrigel is superior to collagen gel (Rawdon and Andrew, 1997). This finding is in line with results of studies on mammalian islet cells that have shown extracellular matrix produced by cultured bovine corneal endothelial cells (Beattie et al, 1991;Hayek et al, 1989) or by a basement membrane-secreting tumour line (Muschel et al, 1986) to improve islet cell function.…”
Section: Effect Of Substrate and Mediumsupporting
confidence: 85%
“…With a view to identification of factors specifically required for differentiation of insulin cells, an in vitro system utilising the dorsal pancreatic bud of the chick embryo has been established (see Andrew et al, 1994;Rawdon and Andrew, 1997;Rawdon and Andrew, 1988). This model system enables the nature of the substrate and medium to be manipulated.…”
Section: In Vitro Studies On Avian Pancreas Donementioning
confidence: 99%
“…(Benjamin Rawdon and Ann Andrew are acknowledged as members of our research group who carried out the earlier work referred to.) Raised levels of glucose and essential amino acids in a fully defined synthetic serum-free medium have been shown to increase the proportions of insulin cells (1.9-fold) in the dorsal pancreatic buds of chick embryos cultured on Matrigel [Rawdon and Andrew, 1997]. Chick pancreatic buds cultured on Matrigel in a serum-free medium supplemented with nicotinamide also showed increased proportions of insulin cells (a 2.5-fold increase) [Mngomezulu and Kramer, 2000].…”
Section: Introductionmentioning
confidence: 97%
“…The proportion of insulin cells that develops in culture has been markedly improved by the use of extracellular matrices and a variety of growth factors or nutrients [Swenne, 1985;Swenne et al, 1987;Otonkoski et al, 1988;Rawdon and Andrew, 1997]. (Benjamin Rawdon and Ann Andrew are acknowledged as members of our research group who carried out the earlier work referred to.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation